The Development of Chemical Modules Based on POE (Predict, Observe, Explain) in the Solution Colligative Properties Subject as a Learning Resources for Senior High School/Equal - yenni, Ervi; Holiwarni, Betty; Haryati, Sri (Proceedings of the UR International Conference on Educational Sciences, 2018)
The study aims to develop POE-based learning resources in the form of modules for senior high school chemistry on the solution colligative properties subject. The research method used is development research. Development research used 4-D model which are carried out in four stage: Define, Design, Development, and Disseminate. In the research only on the stage of development. The developed POE-based learning source prototype was validated by 4 validators, 2 people as experts and 2 people as users. The research data was obtained through a validation sheet filled by the validator. The results of the assessment of the four validators in each aspect assessed by the category are very good.The conclusion shows that the POE-based modules produced for senior high school chemistry learning on solution colligative properties are valid in terms of content and construction.